Penyuluhan Kesehatan Berbasis Daring tentang Hipertensi pada Masa Pandemik Covid-19 - Hendri Tamara Yuda; Ade Fitriani; Lilis Lismayanti; Nur Hidayat (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Hypertension or high blood pressure is an increase in systolic blood ≥140 mmHg and diastolic blood pressure ≥90 mmHg which can cause various other chronic diseases. Online health education is an effort to prevent more severe illness by fulfilling the Health protocol during the covid-19 outbreak. Objective: The purpose of this counseling is to increase public knowledge, especially hypertension sufferers about the basic concepts of disease, management, and behavior modification. Method: The counseling method is done by video call or video conference using a variety of applications that are familiar in the community such as WhatsApp, Instagram, zoom, and google meet. The instrument used was a PowerPoint that contained explanations on topics related to hypertension. The questionnaire was used to measure the knowledge that was processed using SPSS version 24. Result: The results of this study showed that there was a change in the mean value of knowledge before (12.77) and after (17.88) counseling. Conclusion: In conclusion, this health education has a positive impact on increasing the knowledge of hypertension sufferers, so these activities need to be carried out intensively in the wider community.